2006
DOI: 10.1007/s00268-005-0754-x
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal Modified Devascularization Procedure with or without Esophageal Stapler Transection—An Operation Adequate for Effective Control of a Variceal Bleed. Is Esophageal Stapler Transection Necessary?

Abstract: Devascularization without esophageal stapler transection is a safe and effective procedure for adequate (urgent and long-term) control of variceal bleeding with similar results and less morbidity when compared to devascularization with esophageal transection in cirrhotic patients, as well as non-cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
(68 reference statements)
1
19
1
1
Order By: Relevance
“…Previous studies have reported a re-bleeding rate of 7.1–37% in patients undergoing devascularization [21,22], while the re-bleeding rate after undergoing a distal splenorenal shunt is reported to be between 5–15% [1]. The incidence of recurrent variceal bleeding in the SDDS-GSR group in our study was significantly lower than that in the splenectomy with pericardial devascularization (SPD) group.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Previous studies have reported a re-bleeding rate of 7.1–37% in patients undergoing devascularization [21,22], while the re-bleeding rate after undergoing a distal splenorenal shunt is reported to be between 5–15% [1]. The incidence of recurrent variceal bleeding in the SDDS-GSR group in our study was significantly lower than that in the splenectomy with pericardial devascularization (SPD) group.…”
Section: Discussioncontrasting
confidence: 53%
“…First, this procedure uses en bloc resection of the coronary vein branch to prevent postoperative venous recanalization. This procedure also reduces the risk of congestive gastropathy, which is an important cause of postoperative re-bleeding [22]. Second, the splenorenal shunt relieves portal hypertension to some extent and might delay the recurrence of gastroesophageal varices.…”
Section: Discussionmentioning
confidence: 99%
“…Gastropathy is another important source of rebleeding after a PCDV procedure because the PCDV exacerbates the pathologic changes and congestive conditions in the gastric mucosa. The rebleeding rate from portal hypertension gastropathy (PHG) was reported to range from 20.0 to 83.3% postoperatively [30, 32, 33]. In our series, the incidence of gastropathy in the combined group was 5.1%, and it accounted for 20.0% of the total rebleeding rate, rates which were lower than those in the PCDV group, at 16.7 and 36.4% (Table 5).…”
Section: Resultsmentioning
confidence: 64%
“…Although devascularization procedures have been shown to be highly effective for controlling acute variceal bleeding, a significant rebleeding rate of 7.1–37% in cirrhotic patients has been reported after prolonged follow up [11, 29, 30]. In China, the rebleeding rate after PCDV was 13.3–21.09% [31].…”
Section: Resultsmentioning
confidence: 99%
“…In the present series, the incidence of residual (0%) and recurrent 12 (12.53%) varices after extensive devascularization was similar to the figures reported by some authors (37,38) . According to reports in the literature, the rebleeding rate of patients who underwent devascularization was 7.1%-37 % (39) . In our study we had a rebleed in one patient (0.96%) in early post operative while in 7 (6.73%) patients in long term follow up, thus overall rebleed developed in 8 (7.69%) patients.…”
Section: Discussionmentioning
confidence: 99%